Analysis of microbial community diversity in Danyang Huangjiu Jiuqu based on Illumina MiSeq high-throughput sequencing technique - CHEN Lei, DAI Yijun (Zhongguo niangzao)
In this study, the microbial community diversity in Huangjiu Jiuqu from Danyang, Jiangsu was studied by Illumina Miseq high-throughput sequencing technique. The results showed that the diversity of fungal community in the Jiuqu was higher than that of bacterial community, while the richness was lower than that of bacterial community. A total of 7 bacterial phyla, 10 bacterial genera, and 6 fungal phyla, 14 fungal genera were annotated from the sample. Lactobacillus, Weissella, Enterobacter, Staphylococcus, Acinetobacter and Pantoea were the dominant bacterial genera (relative abundance≥1%). Aspergillus, Aureobasidium, Cladosporium, Wickerhamyces, Penicillium, Mrakia, Rhizopus, Fusarium, Sarocladium and Talaromyces were the dominant fungal genera. Among the dominant fungal genera (relative abundance≥1%), Aureobasidium and Talaromyces were less reported in microbial genera of Jiuqu, their characteristics and functions were still not clear and need to be further studied. The results of the study provided a theoretical basis for improving the fermentation process and quality of Danyang Huangjiu.